Mythological and Historical Representation: A Critical Discourse Analysis on Aeschylus’s Poems The Sacrifice of Iphigenia and The Battle of Salamis - Afrianto Afrianto; Wahyu Widianto (Journal of Arts and Education, 2022)
An allusion is a reference to a well-known person, place, event, literary work, or work of art. The main purpose of this research is to find the allusion in the selected poems of Aeschylus The Battle of Salamis and The Sacrifice of Iphigenia and critically analyze the poems to explore and describe the story and mythology behind the expressions in each line. This research is conducted qualitatively and applies purposive sampling to choose and gather the data. It can be reported that both poems represent Greek mythology and history. The representation is derived from expressions, which are in the form of words and sentences. It is found that the allusion found contains names of figures in Greek mythology, such as god-goddess (Artemis), kings (Agamemnon, Atreus), and places (Strymon). These become the references to convey the meaning and to deliver the message of the poems. Regarding these names, the poet connects his idea in the poem to the Greek story and mythology. In addition, there are three functions of allusion confirmed in this research; those are delineating the character, carrying the theme, creating humor. Accordingly, it is noteworthy that allusion can be used to identify the correlation between a particular text and reality, history, and even mythology. In this case, it is noteworthy that allusion is not only a reference, but it also makes expression in the poem more vivid, flowery, interesting, and attractive.